Combinatorial Investigations of Ni-Si Negative Electrode Materials for Li-Ion Batteries. Issue 9 (30th June 2015) - Du, Zhijia; Hatchard, T. D.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Sputtered thin films in the Ni-Si system (0 ≤ x ≤ 0.65 in Nix Si1-x ) were studied for use as anode materials in Li-ion cells. All compositions were found to be amorphous. The Ni in Ni-Si films was found to suppress the lithiation voltage, resulting in a reduction in capacity. The delithiation voltage was not affected. No capacity was observed when Ni content was more than 50 at% because at this composition the lithiation voltage was suppressed to 0 V. In contrast to previous models of capacity in transition metal-Si films, all Si atoms were found to be active in Ni-Si films at all compositions. Capacity reduction is only caused by a suppression of the Si lithiation voltage. We attribute this voltage suppression to internal stress in the thin film during lithiation from the presence of Ni.